(untitled) (International Journal of Environmental Sciences, 2026)
Soft soils such as clay, silt, and organic deposits present significant challenges for civil engineering projects due to their low bearing capacity, high compressibility, and excessive settlement potential. These unfavorable geotechnical properties often threaten the stability and serviceability of infrastructure including highways, embankments, bridges, and building foundations. Consequently, ground improvement techniques have become essential to enhance soil strength, accelerate consolidation, and reduce long-term settlement. This review paper presents a comprehensive analysis of major ground improvement techniques used for soft soil stabilization, focusing on mechanical, chemical, and inclusion-based methods. Mechanical techniques such as preloading, vacuum preloading, and prefabricated vertical drains (PVDs) are widely applied to accelerate consolidation and improve soil density by expelling excess pore water pressure. Chemical stabilization methods, including cement stabilization, lime treatment, deep soil mixing, geopolymers, and bio-based techniques like microbial-induced calcium carbonate precipitation (MICP), modify soil structure through chemical reactions that increase strength and stiffness. Inclusion-based approaches such as stone columns, geosynthetic reinforcement, and reinforced columns improve load transfer mechanisms and reduce settlement by creating composite ground systems. The paper also evaluates performance metrics including settlement reduction, consolidation acceleration, and cost effectiveness based on reported case studies and experimental research. In addition, emerging sustainable technologies such as biodegradable vertical drains, recycled materials, natural fiber reinforcement, and electrokinetic stabilization are examined for their environmental benefits and engineering potential. The findings indicate that hybrid ground improvement systems combining multiple techniques often provide the most effective solutions under complex site conditions.